Kewaspadaan Terhadap Musuh Tersamarkan Dalam Komunitas Kristen: Analisis Alkitabiah Terhadap Ancaman Penyesat Dan Nabi Palsu - Gunarto, Rita Oktavia; Herman, Samuel; Abraham, Jessica Elizabeth (Sekolah Tinggi Teologi Real Batam, 2024)
True Christians build their faith on personal decisions born from spiritual experiences, particularly their belief in Jesus Christ. However, some individuals may join with impure motives, like yeast hidden in dough, which can negatively influence the community. This group includes deceivers, false prophets, and hypocrites who disguise themselves as fellow believers but are, in fact, hidden enemies. In Matthew 16:5-12, Jesus warns His disciples to be vigilant against the